Protective Effect of Moderate Hypotonic Fluid on Organ Dysfunction via Alleviating Lethal Triad Following Seawater Immersion With Hemorrhagic Shock in Rats - Zhu, Yu; Deng, Haoyue; She, Han; Zhou, Yuanqun; Wu, Yue; Zhang, Jie; Liu, Liangming; Tao, Li (Frontiers in Physiology, 2022)
Previous studies found that seawater immersion combination with hemorrhagic shock (SIHS) induced serious organ function disorder, and lethal triad was a critical sign. There were no effective treatments of seawater immersion combination with hemorrhagic shock. Fluid resuscitation was the initial measurement for early aid following hemorrhagic shock, while the proper fluid for SIHS is not clear. Effects of different osmotic pressure (Ringer Lactate, 0.3% saline,0.6% saline, and 0.9% normal saline) on the lethal triad, mitochondrial function, vital organ functions, and survival were observed following seawater immersion combination with hemorrhagic shock in rats. The results showed that SIHS led to an obvious lethal triad which presented the decrease of body temperature, acidosis, and coagulation functions disorder in rats. Different osmotic pressures fluid resuscitation recovered the body temperature and corrected acidosis with different levels, effects of 0.6% normal saline were best, especial for the coagulation function, 0.6% normal saline alleviated lethal triad significantly. Further studies showed that SIHS resulted in the damage of mitochondrial function of vital organs, the increase of vascular permeability, at the same time the organ functions including cardiac, liver, kidney were disordered. Conventional fluid such as LR or 0.9% normal saline could not improve mitochondrial function, vascular leakage and alleviate the damage of organ function. While moderate hypotonic fluid, the 0.6% normal saline, could lighten organ function damage via protecting mitochondrial function including increasing the left ventricular fractional shortening and the left ventricular ejection fraction, decreasing the levels of aspartate transaminase, alanine transferase, blood urea nitrogen, and creatinine in the blood. The effects of different osmotic pressure fluids on the mean arterial pressure (MAP) had a similar trend as above parameters. The survival results showed that 0.6% normal saline group improved the survival rate and prolonged the survival time, the 72-h survival rate was 7/16, as compared with the LR group (3/16). The results indicate that appropriate hypotonic fluid is suitable after SIHS, which alleviate lethal triad, protect mitochondrial function, and organ functions, and prolong the survival time.